Parental Response to Early Human Capital Shocks: Evidence from the Chernobyl Accident - Martina Zweimueller; Martin Halla (University of Duisburg-Essen, CINCH - Health Economics Research Center, 2014)
Little is known about the response behavior of parents whose children are exposed to an early-life shock. We interpret the prenatal exposure of the Austrian 1986 cohort to radioactive fallout from the Chernobyl accident as a negative human capital shock and examine their parents' response behavior. To identify causal effects, we can rely on exogenous variation in the exposure to radioactive fallout (over time and) between communities due to geographic differences in precipitation at the time of the accident. Our design-based approach (which accounts for culling effects) provides robust empirical evidence for compensating investment behavior. Families with low socioeconomic status reduce their family size, while families with higher status respond with reduced maternal labor supply. Our results urge caution in the interpretation of estimates of the long-term effects of early-life shocks on children. These estimates should only be interpreted as reduced-form estimates, and one has to account for parental response behavior to reach a deeper understanding on the relationship between early-life shocks and the formation of human capital. In the case of our application, we can interpret the estimates as the lower bound of the biological effect. For exposed children from higher socioeconomic backgrounds, there are no detrimental effects discernable. In contrast, exposed children from lower socioeconomic backgrounds have significantly worse human capital outcomes as young adults. This suggests that compensating investment by parents with higher socioeconomic status is relatively more effective.
Keywords: I18; I20; Q48; Q53; J24; 330; Fetal origins; parental response; Chernobyl; radiation; health; culling; human capital; fertility; labor supply